2015
DOI: 10.1021/acs.analchem.5b01198
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Size-Determination of Whole Virus Vaccine Particles Using Gas-Phase Electrophoretic Mobility Macromolecular Analyzer, Atomic Force Microscopy, and Transmission Electron Microscopy

Abstract: Biophysical properties including particle size distribution, integrity, and shape of whole virus vaccine particles at different stages in tick-borne encephalitis (TBE) vaccines formulation were analyzed by a new set of methods. Size-exclusion chromatography (SEC) was used as a conservative sample preparation for vaccine particle fractionation and gas-phase electrophoretic mobility macromolecular analyzer (GEMMA) for analyzing electrophoretic mobility diameters of isolated TBE virions. The derived particle diam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 46 publications
3
27
0
Order By: Relevance
“…We found that also the sampling of the SNA–A1AT complex onto the NC membrane showed a noticeable staining comparable to A1AT sample. Interestingly, no distinct spot in the size of the ENAS electrode (9.5 mm diameter) was found, as observed previously after collecting significantly larger particles [16]. In our case, the applied NC membrane was evenly stained, probably due to the fact that the ENAS voltage was not high enough to deviate the particles from their trajectory imposed by the high nDMA sheath flow and to focus them on a distinct area.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…We found that also the sampling of the SNA–A1AT complex onto the NC membrane showed a noticeable staining comparable to A1AT sample. Interestingly, no distinct spot in the size of the ENAS electrode (9.5 mm diameter) was found, as observed previously after collecting significantly larger particles [16]. In our case, the applied NC membrane was evenly stained, probably due to the fact that the ENAS voltage was not high enough to deviate the particles from their trajectory imposed by the high nDMA sheath flow and to focus them on a distinct area.…”
Section: Resultssupporting
confidence: 81%
“…nES GEMMA also allows a size-selective collection of analytes after gas-phase separation for consecutive investigations like microscopic measurements (transmission electron microscopy, TEM; atomic-force microscopy, AFM) or a biological test as an immunologic assay [1416]. For this purpose, the CPC is replaced by an electrostatic nanoparticle sampler (ENAS).…”
Section: Introductionmentioning
confidence: 99%
“…100 nm). We concluded already in a previous study 30 that this is most likely caused by force application of the AFM tip or interaction of particles with the wafer surface, or a combination of both.…”
Section: Resultsmentioning
confidence: 66%
“…A collapse of VLP particles during gas-phase electrophoresis upon stripping of solvent molecules from their interior seems highly unlikely as AFM and dot-blot analyses of a vaccine VLP demonstrated particle integrity after gas-phase electrophoresis [44]. Instead, due to protein analyte inherent M W limitations, especially a direct comparison of a protein correlation with an EMD/M W correlation for VLPs is to date not feasible.…”
Section: Resultsmentioning
confidence: 99%
“…Besides yielding information on analyte surface-dry particle size and size distribution, particle number concentration detection is possible in accordance with recommendations of the European Commission for characterization of nanoparticle material (2011/696/EU from October 18 th , 2011). Furthermore, analytes can be size-selected for further analyses employing orthogonal methods for instance electron microscopy [43], atomic force microscopy [44], spectroscopic techniques [45, 46], or antibody-based nanoparticle recognition [44, 47]. It is of note that LiquiScan ES, MacroIMS, and SMPS are synonyms of the same instrument found in literature.…”
Section: Introductionmentioning
confidence: 99%